Die Afrikaanse gereformeerde kerke in Suid-Afrika en ekologie - Fick, Rikus (Stellenbosch Theological Journal, 2021)
The Afrikaans reformed churches in South Africa and ecology A plethora of studies describing the scope of destruction of the ecology has been published since the 1970s. Lately, Christianity has been accused of being partly responsible for this. Despite the fact that South Africa is one of the ten largest polluters in the world, local religious communities only started voicing an opinion on this matter during the late 1980s. Only in the early 1990s did the reformed churches in South Africa begin some soul searching and the matter was placed on the agenda. The question raised in this article is: What contribution have the reformed churches in South Africa made towards averting this crisis? The author considers criticism levelled at Christianity in general and at the reformed churches in particular; the status of ecology in the dogma of these churches; the contributions made by theologians, and important decisions taken by synods. Three phases were noted in the way the synods dealt with the issue: Firstly, it was acknowledged that a crisis exists and that the church is neither innocent nor can she remain indifferent; secondly, theologians reflected deeply on this matter and offered a refined formulation of a creed to articulate the relationship between God, creation and man. Lastly, practical guidelines were proposed. It was found that the reformed churches have contributed significantly towards alerting people to the fact that the crisis also has religious implications; that the faithful should obey Biblical guidelines; and that there are implications for life, liturgy, education, and theological training.